WOMEN TRAFFICKING DALAM NOVEL AMOI: GADIS YANG MENGGAPAI IMPIAN KARYA MYA YE - Wa Ode Siti Sabania; Nurlailatul Qadriani; Faika Burhan (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
This research aims to describe the trafficking of women in the novel Amoi: The Girl Who Reaches Her Dreams by Mya Ye. This type of research is library research using qualitative descriptive methods, analysis of feminist literary criticism, and socialist feminism as supporting theories. The data in this research are words, phrases, sentences or paragraphs related to the trafficking of women in the novel Amoi: The Girl Who Reaches Dreams by Mya Ye. The results of this research show that women's trafficking occurs because of the patriarchal system and the capitalist system which exploits the bodies of Singkawang women so that they are unconsciously trapped in transnational crime (trafficking). Various forms of women trafficking that occur in Singkawang are through marriage, forced prostitution and forced labor. The basic factors that cause Singkawang women to be trapped in trafficking are poverty and low access to education. Poverty occurs because of two systems: (1) the capitalist system, a system that emphasizes profit and efficiency so that female workers are paid low wages to maintain minimum production costs and maximize profits for capital owners; (2) patriarchal system, a system that places women in the traditional role as housewives who depend on men for their economic needs. Low access to education is caused by: (1) traditional roles which are characteristic of the patriarchal system, causing women to be deemed not to need to receive education and emphasizing women's dependence on men; (2) efforts to